2011
DOI: 10.1111/j.1365-294x.2011.05130.x
|View full text |Cite
|
Sign up to set email alerts
|

The Bantu expansion revisited: a new analysis of Y chromosome variation in Central Western Africa

Abstract: The current distribution of Bantu languages is commonly considered to be a consequence of a relatively recent population expansion (3-5kya) in Central Western Africa. While there is a substantial consensus regarding the centre of origin of Bantu languages (the Benue River Valley, between South East Nigeria and Western Cameroon), the identification of the area from where the population expansion actually started, the relation between the processes leading to the spread of languages and peoples and the relevance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 69 publications
(164 reference statements)
3
39
0
Order By: Relevance
“…As a consequence, this study makes an important contribution to filling the gap. Pakendorf et al 7 identify and provide evidence of greater complexity in the process of the EBSP as suggested by Alves et al 33 and Montano et al 34 …”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…As a consequence, this study makes an important contribution to filling the gap. Pakendorf et al 7 identify and provide evidence of greater complexity in the process of the EBSP as suggested by Alves et al 33 and Montano et al 34 …”
Section: Introductionmentioning
confidence: 60%
“…Recently, Alves et al 33 analysing a battery of 14 DIPSTRs (ie, deletion/ insertion polymorphisms tightly linked to STRs) in 19 Bantuspeaking groups from Mozambique and Angola concluded that it is becoming increasingly difficult to accept models, suggesting an early split between eastern and western Bantu-speaking populations, whereas Montano et al 34 analysing NRY UEPs and STRs in groups from Nigeria, Cameroon, Gabon and Congo concluded that the evolutionary scenario is more complex than previously thought. Our analysis of NRY from groups over a wide geographic area is consistent with both these conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the approach taken by Di Giacomo et al [50], we compared the distribution of NRY variation within E-sY81 (E1b1a; the signature haplogroup of EBSP [19,35,51,52]), a clade that was present in all population samples including Palenque, and observed only in men of RAD. F ST between the Palenque and the other groups, based on the frequencies of the E-sY81 component haplogroups, revealed only two groups with a nonsignificant F ST (Chewa and Yombe) with the Yombe-Palenque F ST , 0.001 (electronic supplementary material, table S6).…”
Section: Results (A) Frequencies Of Nry Haplogroups and Nry-based Genmentioning
confidence: 99%
“…Several studies have suggested that multiple migratory routes of Bantu populations seemingly converged, overlapped, and split during distinct periods of time leading to the spread of Bantu genomes and languages to a great majority in subequatorial Africa (Ansari Pour et al 2013; de Filippo et al 2011, 2012; Montano et al 2011; Plaza et al 2004). Given the extensive and intricate nature of population expansions that spanned across Africa the precise geographic deduction of the ancestral origin of Siddi genomes had so far remained elusive (Narang et al 2011).…”
Section: Discussionmentioning
confidence: 99%